(untitled) (Global Journal of Science Frontier Research, 2012)
The materials are essential for critical performance of electronic products Disposal of some of these materials however poses a serious threat to the environment after endof- life of the product The European Union and other developed countries have already enacted legislative measures as Restriction of Hazardous Substances RoHS Directive to restrict the use of certain substances in the manufacturing of the electronic products India has also notified similar legislation on 12th May 2011 to address this serious issue Indian electronic manufactures are however facing serious challenges due to this legislative restriction Industry needs testing and certification of admissible level of hazardous substances in the product for necessary compliance The testing facilities available with few private laboratories are not adequate Department of lectronics and Information Technology Government of India has therefore created a state-of-art laboratory with modern analytical instruments to address the growing demand of the industry This article provides an overview of the RoHS and other related legislative measures present in the world and in India An attempt is also made to study the preparedness of the industry and the immediate impact on the business of electronic sector